Corporate tax planning, the use of SPV, board independence, and firm value - Suriawinata, Iman Sofian; Almurni, Siti (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
Although many studies discuss the significant role of special purpose vehicles (SPVs) in the corporate tax planning context, no prior empirical research exists on the value relevance of such use. Our study fills the gap by investigating the impact of the use of SPVs in corporate tax planning on firm value. Since tax planning is a risky endeavor, of particular interest is the role of corporate governance mechanisms in ensuring that firms select optimal levels of corporate tax planning activities and preventing managerial diversion of tax-saving related cash flows. Using moderated regression analysis on a sample of 119 listed non-financial firms from 2013 to 2017, we find that the use of SPVs in corporate tax planning enhances firm value and that corporate tax planning moderated by board independence also increases firm value.